Design Of Automatic Rest Api Testing Framework Using Behavioral Driven Development Approach - Setiawan, Andres; Haryono, Haryono (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
REST API is an interface that allows components to interact and exchange information over a network. Testing REST API is essential to ensure the reliability of interactions between components. This research discusses the framework for automatic REST API testing using Behavioral Driven Development. The research begins with the creation of test cases, which are then processed into a designed framework for automatic testing based on the created test cases. Ultimately, the automatic REST API testing framework will generate and display a test report that includes information such as testing status, results, and duration. The focus of the research is to produce a generic REST API testing framework that can be adopted by various REST APIs and easily implemented in the transition process from manual to automatic testing. This automatic REST API testing framework can reduce testing time by 93.67% compared to manual testing. Based on survey data, 7 out of 10 respondents said that the automatic testing framework is very easy to learn and use. The survey data also reveals that 9 out of 10 respondents have seen the benefits of the automatic REST API testing framework that was created for this research.